Islamic Education and Global Ecological Challenges: An Eco-Theological Approach to the Environmental Crisis in the Folu Sector - Afriandi, Afriandi; Ulfa, Siti Afifa; Syarah, Asnila; Akmaulia, Marsella; Al-Wakia, Andi Fikra; Najiah, Didi Firqatun Najiah (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This study aims to examine the role of ecotheology-based Islamic education in responding to global environmental crises, especially in the Forest and Other Land Use (FoLU) sector as well as the NetSink 30 mitigation program. Using a qualitative approach through library research methods, this study explores Islamic values such as monotheism, amanah, and mizan that are integrated into Islamic educational curricula and practices to build awareness and environmental conservation actions. The results of the study show that Islamic education not only shapes believing individuals, but also instills ecological awareness as part of human moral responsibility as a caliph on earth. The ecotheology approach emphasizes harmony between humans and nature and encourages the implementation of sustainable practices related to FoLU management. The study provides a theoretical foundation and practical recommendations for educators, policymakers, and the Muslim community to integrate ecological values in Islamic education, thereby supporting a holistic and sustainable climate change mitigation agenda.